Ethnohistory: a review of the method and its applicability to the study of rural Malaysia. - S.M. Childs. (Universiti Kebangsaan Malaysia, 1974)
Ethnohistory is a methodological approach to the study of socio-cultural behavior which combines the strengths of ethnographic and historical research. The thesis of this paper is that such an approach offers an integrated perspective of social process not obtainable otherwise, therefore representing a valuable methodological tool to the anthropologist studying socio-cultural change. Malaysia, whose historical background of cultural change and culture contact is richly documented, offers great potential for ethnohistorical research.